Genome‐wide and molecular evolution analysis of the Poplar KT/HAK/KUP potassium transporter gene family - He, Caiyun; Cui, Kai; Duan, Aiguo; Zeng, Yanfei; Zhang, Jianguo (Ecology and evolution, 2012)
As the largest K + transport gene family, KT/HAK/KUP family plays an important role in plant growth, development, and stress adaptation. However, there is limited information about this family in woody plant species. In this study, with genome‐wide in‐depth investigation, 31 Poplar KT/HAK/KUP transporter genes including six pairs of tandem duplicated and eight pairs of segmental duplicated paralogs have been identified, suggesting segmental and tandem duplication events contributed to the expansion of this family in Poplar. The combination of phylogenetic, exon structure and splice site, and paragon analysis revealed 11 pairs of Poplar KT/HAK/KUP duplicates. For these 11 pairs, all pairs are subject to purify selection, and asymmetric evolutionary rates have been found to occur in three pairs. This study might provide more insights into the underlying evolution mechanisms of trees acclimating to their natural habitat. In this study, with genome‐wide in‐depth investigation, 31 Poplar KT/HAK/KUP transporter genes including six pairs of tandem duplicated and eight pairs of segmental duplicated paralogs have been identified, suggesting segmental and tandem duplication events contributed to the expansion of this family in Poplar.